Islamization of Education at School level in Pakistan and its Ramifications: A Critical Understanding: Implications of Islamization of Education in Pakistan (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Islamic ideology permeating the entire education system of Pakistan is one of the serious issues confronting the state of Pakistan, with an increasing emphasis on religion with lesser rooms for pluralism and secularism. The muddle was brought about as the result of the various policy initiatives undertook by the various governments of Pakistan since the 1960s. This paper highlights the policy provision, constitutional and legal provision for the Islamization of education and its ramifications in Pakistan. It also evaluates various textbooks and curricula of various Pakistani school boards. Specifically, this study reveals that the focus of the Pakistani education system is not to produce a global citizen with the ability to think rationally and logically but to produce a practising Muslim. The paper concludes that education in Pakistan promotes hatred, insensitivity towards the religious diversity of the nation it also incites to militancy and violence, intolerance, and discrimination towards fellow citizens, and glorify war.